2018
DOI: 10.1111/apt.14823
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: recurrence of hepatocellular carcinoma following direct‐acting antiviral therapy

Abstract: Current data suggest acceptable HCC recurrence rates after DAA therapy, particularly if DAA therapy is delayed at least 6 months after HCC complete response. However, data characterising HCC recurrence after DAA therapy are of limited quality, highlighting the need for high quality prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 50 publications
2
62
0
10
Order By: Relevance
“…Substantial variation in the design of these and several subsequent studies makes it difficult to estimate the true rate of HCC recurrence following DAA therapy. Indeed, in a recent meta-analysis that included 26 studies, there was significant statistical heterogeneity in reported rates of recurrence (37)The pooled estimate of the proportion of patients with HCC recurrence after DAA therapy was 25.1% (95% CI 19.431.2%) but ranged from 0% to as high as 59%. There was also variability in the duration of follow-up across studies (2.5 to 35.7 months), time between HCC treatment and initiation of DAA therapy, modality of tumor treatment, and the proportion of patients with non-early-stage HCC or multiple prior recurrences.…”
Section: Daa Treatment and Recurrent Hccmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial variation in the design of these and several subsequent studies makes it difficult to estimate the true rate of HCC recurrence following DAA therapy. Indeed, in a recent meta-analysis that included 26 studies, there was significant statistical heterogeneity in reported rates of recurrence (37)The pooled estimate of the proportion of patients with HCC recurrence after DAA therapy was 25.1% (95% CI 19.431.2%) but ranged from 0% to as high as 59%. There was also variability in the duration of follow-up across studies (2.5 to 35.7 months), time between HCC treatment and initiation of DAA therapy, modality of tumor treatment, and the proportion of patients with non-early-stage HCC or multiple prior recurrences.…”
Section: Daa Treatment and Recurrent Hccmentioning
confidence: 99%
“…Compared to IFN-treated patients, the incidence of recurrent HCC was not higher in patients treated with DAAs following curative HCC treatment in two Japanese cohort studies (40, 41). In a meta-analysis of studies that compared DAA-treated and untreated patients with respect to HCC recurrence, DAA treatment was associated with a lower risk of recurrence with a pooled odds ratio of 0.55 (95% CI 0.250.85) (37). A meta-analysis and meta-regression of studies comparing HCC recurrence after DAAs versus IFN found no difference after adjusting for age and follow-up time (7), but was limited by lack of individual patient data, inability to properly adjust for confounders and very large differences in follow-up time between the DAA and IFN studies.…”
Section: Daa Treatment and Recurrent Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent meta-analysis concluded that the HCC occurrence and recurrence rates were comparable between DAA-and IFN-treated patients regardless of the higher SVR rate of the DAA regimen [10]. Moreover, several reports with single-arm DAA-treated HCV-HCC patients declared abruptly increased HCC recurrence rate after antiviral treatment [11][12][13][14], while conflicting results have been reported in other studies comparing to the untreated [15][16][17][18][19][20][21][22][23][24][25] or IFN-treated groups [10,21,[26][27][28][29][30]. Concerns have been raised about the benefit and the timing of adjuvant DAA-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies consisted of an IFN-containing DAA regimen [27,28] and did not adjust for baseline characteristics before comparison [26,30]. The definition of follow-up duration varies across these studies [10,21,[23][24][25][26][27][28][29][30] and may lead to inconsistent or conflicting comparison results [31]. We therefore conducted this nested case-control study, using propensity score matching (PSM) to adjust for the confounders, and with application of different follow-up time frames to investigate if the tertiary prevention effect is different between the DAA and PegIFN/RBV regimens in curative CHC-HCC patients.…”
Section: Introductionmentioning
confidence: 99%